Modern analysis of customer surveys : with applications using R - Kenett, Ron.; Salini, Silvia (Chichester : John Wiley & Sons, 2012)
This book introduces customer satisfaction surveys, with focus on the classical problems of analysing them, which include; missing values, outliers, sampling techniques, integration of different data sources, as well as modern and non-standard tools. Each chapter describes, in detail, a different technique that is applied to the standard data set along with R scripts featuring on a supporting website. Most of the techniques featured in this book are applied to a standard set of data collected from 266 companies (customers) participating in the Annual Customer Satisfaction Survey (ACSS) of a global company. The data refers to a questionnaire consisting of 81 questions that covered a wide range of service and product perspectives.
Front Matter -- Basic aspects of Customer Satisfaction Survey Data Analysis. Standards and Classical Techniques in Data Analysis of Customer Satisfaction Surveys / Silvia Salini, Ron S Kenett -- The ABC Annual Customer Satisfaction Survey / Ron S Kenett, Silvia Salini -- Census and Sample Surveys / Giovanna Nicolini, Luciana Dalla Valle -- Measurement Scales / Andrea Bonanomi, Gabriele Cantaluppi -- Integrated Analysis / Silvia Biffignandi -- Web Surveys / Roberto Furlan, Diego Martone -- The Concept and Assessment of Customer Satisfaction / Irena Ograjen\208Dek, Iddo Gal -- Missing Data and Imputation Methods / Alessandra Mattei, Fabrizia Mealli, Donald B Rubin -- Outliers and Robustness for Ordinal Data / Marco Riani, Francesca Torti, Sergio Zani -- Modern Techniques in Customer Satisfaction Survey Data Analysis. Statistical Inference for Causal Effects / Fabrizia Mealli, Barbara Pacini, Donald B Rubin -- Bayesian Networks Applied to Customer Surveys / Ron S Kenett, Giovanni Perruca, Silvia Salini -- Log-Linear Model Methods / Stephen E Fienberg, Daniel Manrique-Vallier -- CUB Models: Statistical Methods and Empirical Evidence / Maria Iannario, Domenico Piccolo -- The Rasch Model / Francesca De Battisti, Giovanna Nicolini, Silvia Salini -- Tree-Based Methods and Decision Trees / Giuliano Galimberti, Gabriele Soffritti -- PLS Models / Giuseppe Boari, Gabriele Cantaluppi -- Nonlinear Principal Component Analysis / Pier Alda Ferrari, Alessandro Barbiero -- Multidimensional Scaling / Nadia Solaro -- Multilevel Models for Ordinal Data / Leonardo Grilli, Carla Rampichini -- Quality Standards and Control Charts Applied to Customer Surveys / Ron S Kenett, Laura Deldossi, Diego Zappa -- Fuzzy Methods and Satisfaction Indices / Sergio Zani, Maria Adele Milioli, Isabella Morlini -- Appendix: An Introduction to R -- Index.
MNS
Keywords: Consumer satisfaction -- Research -- Statistical methods; Consumer satisfaction -- Evaluation; Consumers -- Research -- Statistical methods; Consumers -- Research -- Data processing; Sampling (Statistics) -- Evaluation; Surveys -- Statistical methods; Surveys -- Data processing